ANALISIS STRATEGI PEMECAHAN MASALAH SISWA PADA MATERI BILANGAN BERPANGKAT DAN BENTUK AKAR BERDASARKAN LANGKAH POLYA - Alifia Salsabila; Aan Hasanah; Tatang Herman (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines students’ problem-solving strategies on Exponents and Radicals using Polya’s framework. Employing a qualitative descriptive approach, the research involved 31 ninth-grade students at a public junior high school in Bandung. Data were collected through essay tests, interviews, and documentation, and analyzed following Miles & Huberman’s interactive model, including data reduction, display, and conclusion drawing. Findings indicate that high-ability students successfully applied all four of Polya’s steps, though minor errors were observed during the reviewing stage. The most significant weaknesses were in the “carrying out the plan” (56.98%) and “reviewing” (41.93%) stages, underscoring the need to enhance students’ strategic and metacognitive skills. The study recommends instructional approaches that emphasize problem-solving strategies and metacognitive regulation to improve students’ effectiveness in mathematical problem solving.